International practice, national context and issues for public private partnership in implementation of science and technology tasks in Vietnam - Hung, Nguyen Vo (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Public Private Partnership (PPP) in co-financing science and technology (S&T) tasks has been considered by the Party and the State as an important solution to strengthen the linkage between S&T institutions with businesses in the implementation of applied research, technological innovation, human resources development. Research on international practice shows that the concept of PPP has been used in many areas with a very different and confusing meaning. In science, technology and innovation (STI), PPP concept is also used to refer to a diversified public-private interaction. Each specific PPP design depends on the type of issue to be addressed, the context, conditions, cooperative capacity of the parties involved. This article analyzes the international practice of PPP in STI activities, mainly from the US and EU, and based on that, it makes assessment on the context to identify issues of PPP in STI activities appropriate to Vietnam in the next 10-year period. Code: 16022201<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">